Fortalecimiento de la identidad cultural en los centros educativos: "Inti Ñan, República del Ecuador, Manzana Pamba y Katitawa del pueblo Salasaka" del cantón Pelileo, provincia de Tungurahua. - Masaquiza Masaquiza, Ángel Rufino (2014)
According to the results of surveys conducted in the context of the research are briefly summarized: The work presented here has been carried out the survey and analysis of the situation on cultural identity, where the institution is located, "Inti Nan, Republic of Ecuador, Apple Pamba and the People Katitawa Salasaca" canton Pelileo Tungurahua province, the same that is intended to determine the problems faced today.